2016
DOI: 10.3109/0886022x.2016.1162062
|View full text |Cite
|
Sign up to set email alerts
|

The association of the Klotho polymorphism rs9536314 with parameters of calcium-phosphate metabolism in patients on long-term hemodialysis

Abstract: Background: Patients on long-term hemodialysis frequently suffer from complications, such as secondary hyperparathyroidism, bone fractures, and arteriosclerosis. The process of regulating Ca/P metabolism depends on factors, such as FGF23 and Klotho. This study aimed to answer the question of whether the Klotho polymorphism rs9536314 is associated with FGF23 plasma concentration. Methods: In 118 patients undergoing hemodialysis, blood was collected before and after hemodialysis. The following parameters were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Analyses of alleles and genotypes crude frequencies of nine SNPs of genes codifying for key cytokine and receptors involved in kidney damage pathogenesis do not allow to identify associations with the Klotho, in spite of the above-mentioned data on the role of rs577912 polymorphism as risk factors of mortality in dialyzed patients [13] and the role of rs9536314 in the so-called longevity trait [17]. In a study performed in 2016, it was shown that the GG genotype is associated with reduced survival and poor prognosis in dialysis patients compared to the TT and TG genotypes [18] but we were unable to confirm this observation in our population. Similarly, FGF23 rs7955866 and IGF1 rs35767 were not found to be associated with ESRD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of alleles and genotypes crude frequencies of nine SNPs of genes codifying for key cytokine and receptors involved in kidney damage pathogenesis do not allow to identify associations with the Klotho, in spite of the above-mentioned data on the role of rs577912 polymorphism as risk factors of mortality in dialyzed patients [13] and the role of rs9536314 in the so-called longevity trait [17]. In a study performed in 2016, it was shown that the GG genotype is associated with reduced survival and poor prognosis in dialysis patients compared to the TT and TG genotypes [18] but we were unable to confirm this observation in our population. Similarly, FGF23 rs7955866 and IGF1 rs35767 were not found to be associated with ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Klotho polymorphisms involved in metabolic disorders and cardiovascular pathologies might play a role in favoring progression to ESRD. In particular, rs564481 and rs9536314 might play a role, being implied in metabolic diseases and potentially influencing the prognosis of CKD [ 15 , 16 , 17 , 18 ]. In particular, rs56481 might influence hypertension susceptibility and creatinine serum levels in different populations [ 15 , 16 , 17 ] whereas rs9536314 might influence the kidney failure susceptibility impinging on the kidney function decline due to aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is limited to candidate gene association studies, which have significant issues with reproducibility and publication bias. Studies looked for SNP associations with hemodialysis outcomes including vascular access issues, 56 - 61 biochemical indices, 62 - 65 inflammation, 66 - 68 cardiovascular comorbidities 66 , 69 - 75 and mortality 76 - 79 and PD outcomes including peritoneal transport characteristics, 80 - 84 peritonitis risk, 85 - 87 or risk of encapsulating peritoneal sclerosis 88 ( Supplemental Table 1 ). Sample sizes were inadequate to confidently identify variants of reasonable effect sizes (average sample size of 246, range 67-777 patients).…”
Section: Reviewmentioning
confidence: 99%
“…-Wnt pathway drives cardiac fibrosis in individuals with CKD. As Zhou et al showed, klotho's full-length and secreted form are hostile to Wnt/β-catenin activity, TA B L E 1(Marchelek-Myśliwiec et al, 2016;Nazarian et al, 2017;Valdivielso et al, 2019) …”
mentioning
confidence: 99%